'Doing more with less': a qualitative investigation of perceptions of South African health service managers on implementation of health innovations. Issue 2 (12th March 2019) - Brooke-Sumner, Carrie; Petersen-Williams, Petal; Kruger, James; Mahomed, Hassan; Myers, Bronwyn
Abstract: Building resilience in health systems is an imperative for low- and middle- income countries. Health service managers' ability to implement health innovations may be a key aspect of resilience in primary healthcare facilities, promoting adaptability and functionality. This study investigated health service managers' perceptions and experiences of adopting health innovations. We aimed to identify perceptions of constraints to adoption and emergent behaviours in response to these constraints. A convenience sample of 34 facility, clinical service and sub-district level managers was invited to participate. Six did not respond and were not contactable. In-depth individual interviews in a private space at participants' place of work were conducted with 28 participants. Interviews were audio recorded and transcribed verbatim. NVivo 11 was used to store data and facilitate framework analysis. Study participants described constraints to innovation adoption including: staff lack of understanding of potential benefits; staff personalities, attitudes and behaviours which lead to resistance to change; high workload related to resource constraints and frequent policy changes inducing resistance to change; and suboptimal communication through health system structures. Managers reported employing various strategies to mitigate these constraints. These comprised (1) technical skills including participatory management skills, communication skills, community engagement skills and programme monitoring and evaluation skills, and (2) non-technical skills including role modelling positive attitudes, understanding staff personalities, influencing perceptions of innovations, influencing organizational climate and building trusting relationships. Managers have a vital role in the embedding of service innovations into routine practice. We present a framework of technical and non-technical skills that managers need to facilitate the adoption of health innovations. Future efforts to build managers' capacity to implement health innovations should target these competencies.